Test of Escherichia Coli and Total Microbes on Burger Meat Sold in Kedinding and Pogot Villages, Surabaya, East Java - Tuljannah, Jamila; Hartati, Fadjar Kurnia (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
A burger is a type of fast food that consists of a bun in the middle that contains a patty (ground beef), vegetables, and some sauce. There are several parameters in determining food quality and safety, one of which is analyzing the content of microbiology such as bacteria, viruses, and protozoa in food. Biological hazards, especially in food, need special attention because they are often the causative agents of food poisoning cases. This study aims to determine Eschericia coli contamination and Total Plate Number (TPC) in burger meat samples sold in Kedinding and Pogot villages, Surabaya, East Java. This research is observational with a cross sectional approach. The inspection method used to determine Escherichia coli contamination and the Total Plate Count (TPC) is the Most Likely Number method to determine E. coli and the Total Plate Count (TPC). The results of this study showed that there was no E. coli in all burger meat samples and there were 6 burger meat samples contaminated with bacteria, namely in Samples A, B, C, G, H and I, which exceeded the contamination limit according to to SNI 8503 (2018).